Nutrition & diet therapy - Roth, Ruth A. (Clifton Park, New York : Thomson/Delmar Learning, 2007)
In our health-conscious society, the link between good nutrition and good health is seen everywhere, from magazine and newspaper headlines to television shows and web sites. This presents a challenge to nurses when working to help clients improve their nutrition and health. This work helps you learn the essentials about nutrition and good health.
Chapter 1: The Relationship of Nutrition and Health -- Chapter 2: Planning a Healthy Diet -- Chapter 3: Digestion, Absorption, and Metabolism -- Chapter 4: Carbohydrates -- Chapter 5: Lipids, or Fats -- Chapter 6: Proteins -- Chapter 7: Vitamins -- Chapter 8: Minerals -- Chapter 9: Water -- Chapter 10: Food-Related Illnesses and Allergies -- Chapter 11: Diet During Pregnancy and Lactation -- Chapter 12: Diet During Infancy -- Chapter 13: Diet During Childhood and Adolescence -- Chapter 14: Diet During Young and Middle Adulthood -- Chapter 15: Diet During Late Adulthood -- Chapter 16: Diet and Weight Control -- Chapter 17: Diet and Diabetes Mellitus -- Chapter 18: Diet and Cardiovascular Disease -- Chapter 19: Diet and Renal Disease -- Chapter 20: Diet and Gastrointestinal Problems -- Chapter 21: Diet and Cancer -- Chapter 22: Diet and Clients with Special Needs -- Chapter 23: Nutritional Care of Clients
Includes bibliographical references and index.
Keywords: DIET THERAPY